Goblin war - Hines, Jim C. (Hines, Jim C. Jig the Goblin series, 2008)
After surviving an adventurers' quest against a dragon, a necromancer, and a pixie invasion, goblin Jig Dragonslayer is thrust back into the thick of things when the goblins' lair is invaded by human warriors.